Prevalence of normal TSH value among patients with autonomously functioning thyroid nodule. (1st June 2015) - Treglia, Giorgio; Trimboli, Pierpaolo; Verburg, Frederik A.; Luster, Markus; Giovanella, Luca
Abstract Background International guidelines significantly diverge on the effectiveness of thyroid scintigraphy (TS) in the initial work‐up of thyroid nodules. In particular, the role of TS to detect or exclude the presence of autonomously functioning thyroid nodules (AFTN) in patients with normal serum thyrotropin (TSH) is still a matter to debate. Here, we aimed to review the literature on the prevalence of normal TSH value among patients with AFTN and meta‐analyse data of the retrieved eligible papers. Materials and Methods A comprehensive literature search of studies published from January 2000 to December 2014 on AFTN detected by TS was performed. Records reporting serum TSH values in AFTN were selected. Pooled prevalence of AFTN with normal TSH values was calculated on a per‐patient analysis including 95% confidence intervals (95% CI). Results Eight records including 2761 AFTN were selected for the meta‐analysis. Pooled prevalence of AFTN with normal TSH detected by TS was 50% (95% CI: 32–68%). Selection bias in the included studies and heterogeneity among studies were potential limitations of the meta‐analysis. Conclusions Present meta‐analysis shows that about one in two patients with AFTN demonstrated by TS has a TSH value within normal references. As a consequence, TSH measurement may not be considered as effective as a single tool to detect or exclude AFTN, and TS remains mandatory.